标签:
1 0-1律
A + 0 = A A · 0 = 0 A + A = A A · A = A A‘‘ = A
A + 1 = 1 A · 1 = A A + A‘ = 1 A · A‘ = 0
2 交换律和结合律
A + B = B + A (A + B) + C = A + (B +C)
A · B = B · A (A · B) · C = A · (B · C)
3 分配律和反演律
A · (B + C) = A · B + B · C (A + B + C + ... )‘ = A‘ · B‘ · C‘ · ...
A + B · C = (A + B) · (A + C) (A · B · C · ...)‘ = A‘ + B‘ + C‘ + ...
4 吸收律
A + A · B = A A + A‘ · B = A + B (A +B) · (B + C) = A + B · C
A · (A + B) = A
5 恒等式
AB + A‘C + BC = AB + A‘C
AB + A‘C + BCD = AB + A‘C
标签:
原文地址:http://www.cnblogs.com/xinxue/p/5222226.html